INVESTMENT PROVISION OF INNOVATION ACTIVITY: ESSENCE AND PRINCIPLES - PETROVSKYI, Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents the results of a study aimed at developing theoretical foundations for investment support of innovative activity, including the definition of its essence and principles. The qualitative research methods used were mainly comparative and critical analysis, generalization, abstraction, and induction. A critical review of scientific publications clarified the essence of investment support and its principles. Analysis of previous scientific research results showed the following approaches to define the essence of the category "investment provision for innovative activity": resource, organizational, and process. The scientific novelty of the study includes substantiating the author’s definition of the essence of investment provision of innovative activity based on a combination of the mentioned approaches as a set of investment resources, mechanisms, practical actions, and processes for the formation, accumulation, distribution, investment, and reproduction of resources for generation, production, implementation, sales and dissemination of innovation. Considering modern macroeconomic, technological, and social trends, the following principles of investment provision for innovative activities were determined: accessibility, sufficiency, resilience and reliability, economic efficiency, timeliness, systemic complexity, risk management, adaptability, partnership, environmental, and social responsibility. The possibilities of applying the proposed definition and principles to develop an organizational and economic mechanism for investment provision of innovative activities for economic systems of different levels constitute the practical significance of the author’s finding. Further scientific developments may include research of various countries’ experiences and the development of an organizational and economic mechanism for investment provision of innovative activities that meet the defined principles.